2021
DOI: 10.3390/molecules26206220
|View full text |Cite
|
Sign up to set email alerts
|

A Promiscuous Halogenase for the Derivatization of Flavonoids

Abstract: Halogenation often improves the bioactive properties of natural products and is used in pharmaceutical research for the generation of new potential drug leads. High regio- and stereospecificity, simple reaction conditions and straightforward downstream processing are the main advantages of halogenation using enzymatic biocatalysts compared to chemical synthetic approaches. The identification of new promiscuous halogenases for the modification of various natural products is of great interest in modern drug disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…[5] If other halogenated salts are used instead of sea salt in the production medium, isocoumarin containing the added halogen might be obtained under the action of halogenase. [6] Since some compounds containing bromine exhibited good biological activity, [7] it is worth trying to add bromine salt. In this work, based on the one strain many compounds strategy, we found that this strain could produce more abundant and more active secondary metabolites when adding bromine salt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] If other halogenated salts are used instead of sea salt in the production medium, isocoumarin containing the added halogen might be obtained under the action of halogenase. [6] Since some compounds containing bromine exhibited good biological activity, [7] it is worth trying to add bromine salt. In this work, based on the one strain many compounds strategy, we found that this strain could produce more abundant and more active secondary metabolites when adding bromine salt.…”
Section: Introductionmentioning
confidence: 99%
“…And several compounds including a new chlorinated isocoumarin named 5‐chloro‐6,7‐dihydroxy‐3,8‐dimethylisocoumarin produced by this strain have been reported by us [5] . If other halogenated salts are used instead of sea salt in the production medium, isocoumarin containing the added halogen might be obtained under the action of halogenase [6] . Since some compounds containing bromine exhibited good biological activity, [7] it is worth trying to add bromine salt.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization of the IPS production in TT01 leads to the opportunity to also produce high amounts of stilbene derivatives. However, the production of halogenated CA or IPS without supplementation of the cultures with CA-derivatives was not successful although genes encoding for enzymes incorporating phenol modifying tailoring enzymes like the halogenases radH from the fungus Chaetomium chiversii and dklH from the Grampositive bacterium Frankia alni were expressed (data not shown) 166,167 . One crucial part of the optimization of IPS titers relied on the overproduction of phenylalanine and CA which would not be a sufficient approach, if the production of derivatives like the halogenated IPS are desired since so far no suitable halogenase is known.…”
Section: Outlook On Further Optimizationmentioning
confidence: 99%